Treatment failure of dihydroartemisinin/piperaquine for plasmodium falciparum malaria, Vietnam - Phuc, B; Rasmussen, C; Duong, T; Dong, L; Loi, M; Ménard, D; Tarning, J; Bustos, D; Ringwald, P; Galappaththy, G; Thieu, N (Centers for Disease Control and Prevention, 2017)
We conducted a study in Binh Phuoc, Vietnam, in 2015 on the therapeutic efficacy of dihydroartemisinin/piperaquine for Plasmodium falciparum malaria. A high number of treatment failures (14/40) was found, and piperaquine resistance in Vietnam was confirmed. A change in the malaria treatment policy for Vietnam is in process.